Laura Carlevaris (2024). L'Ottica di Claudio Tolomeo nella storia della prospettiva. Roma: Quasar (diségno, 2025)
Laura Carlevaris’s volume L’Ottica di Claudio Tolomeo nella storia della prospettiva (Claudius Ptolemy’s Optics in the history of perspective), published in 2024 by Edizioni Quasar of Rome –specialized in the fields of Antiquities and Archaeology– has been available since 2024 on the digital platform Torrossa, in digital format. [read more]